REFRAMING THE CANADIAN OIL SANDS - Patchett, Merle; Lozowy, Andriko J (Imaginations: Journal of Cross-Cultural Image Studies, 2012)
“Reframing the Canadian Oil Sands” is a collaborative exchange between photographer Andriko Lozowy and cultural geographer Merle Patchett that engages photography and photographic theory to evoke a more critical and politically meaningful visual engagement with the world’s largest capital oil project. Since the appearance of Edward Burtynsky’s aerial and abstracted photographic-mappings of the region, capturing the scale of the Oil Sands from ‘on high’ has become the dominant visual imaginary. As a result, the dominant visual culture of Fort McMurray oil production is one of nullification or an erasure of representation. For the past five years Lozowy has been engaged in a photographic project—entitled Where is Fort McMurray?—which aims to explore and workwith this sense of erasure by attempting to capture the shifting (and shifted) landscapes of the Alberta Oil Sands from the roadside. For this special issue ofImaginationson “Sighting Oil”, Patchett and Lozowy have curated a set of Lozowy’s photographs to present an alternative, on-the-ground, view of Oil Sands production sites. Through both Lozowy’s images and Patchett’s framing curatorial essay, they explore the disruptive potential of the image and the capacity of photography to both neutralize and energize political engagement with the Canadian Oil Sands.”